(untitled) (World Bulletin of Public Health, 2022)
38 newborns were examined, the functional state of the kidneys was assessed depending on the presence of maternal preeclampsia. It was revealed that in all newborns, there is a decrease in diuresis, a decrease in the osmotic concentration of urine, which increases by the end of the first week of life, but does not reach the indicators of healthy children, while the most pronounced changes are observed in the group of children born from mothers with preeclampsia, and are accompanied by azotemia , which is associated with catabolic processes in the body and reduced renal excretion of nitrogenous products.